Becoming Frederick Douglass [videorecording (DVD)] - Seidlitz, Anne; Pierce, Wendell (PBS, 2022)
Becoming Frederick Douglass is the inspiring story of how a man born into slavery became one of the most prominent statesmen and influential voices for democracy in American history. Born in 1818 on Maryland's Eastern Shore, he escaped from slavery in 1838 and went on to become the most well-known leader of the abolitionist movement.